Effects of Fever Vine (Paederia Linearis Hook.F) Extracts on Inhibition of Salmonella in vitro System - BOUNYAVONG, Somphanh; ONPHACHANH, Xaykham; CHANTHAKHOUN, Vongpasith; KANDEE, Thanousinh; VILAYSACK, Visam; DUANGVICHITH, Khamla; BOUNPHONG , Soysouvanh; MANIVANH, Khone (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The aim of the present study was evaluated the percentage of extracted production; to compare of the inhibition of the growth of Salmonella, and to identify the minimum inhibitory concentation (MIC) of Fever Vine (Paederia Linearis Hook.F) extracted by water, 95% Ethanol, and 99% Methanol. This experiment was conducted in the laboratory by in vitro techniques and randomly assigned by Completely Randomized Design (CRD), followed by 5 treatment groups and 3 replications as: C1 (Positive Control); C2 (penicillin); T1 (water extract), T2 (95% Ethanol) and T3 (99% Methanolic extract). All data were collected and analyzed by Program Sirichai Statistic version 6.0 (2007). The results demonstrated that the extracted production was significant different (p<0.05), the ethanolic and methanolic extract had higher percentage than water extract as 13.19; 13.13 and 4.72% respectively. The extracts of this herb were tested; that can be found the water, ethanolic and methanolic extracts of Fever Vine exhibited antibacterial activity against Salmonella, though the methanolic extract had slightly higher activity. The inhibition zone ratio when compared to penicilline was shown that, methanolic extract had larger than water and ethanolic extracts as 0.408; 0.195 and 0.186 respectively. The MIC values of this extract against the Salmonella varied from 0.1 to 1 g/ml. The result found that these extracts had MIC values at 0.5 g/ml. It can be concluded that Fever Vine (Paederia Linearis Hook.F) has the great potential to provide an effective control for salmonellosis or completely inhibit the growth of salmonella and which may replace antibiotic.